PENGARUH PAJAK TANGGUHAN DAN INTENSITAS ASET TETAP TERHADAP PENGHINDARAN PAJAK DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL MODERASI - Sumayyah; Supriadi, Adi (Publika Citra Media, 2025)
This research aims to examine the effect of Deferred Tax and Fixed Asset Intensity on Tax Avoidance with Financial Performance as a moderating variable. This research uses a quantitative approach and uses associative methods. The type of data used in this research is secondary data. The data analysis method used in this research is Panel Data Regression Analysis using the Eviews version 12 application. The population used in this research is 3 (three) Manufacturing Company sectors listed on the Indonesia Stock Exchange (BEI) for the 2019-2023 period. The data collection technique in this research is a purposive sampling technique with a population of 401 companies becoming the final 14 company samples or 70 observation data processed in this research. The research results show that partially deferred tax has no effect on tax avoidance and fixed asset intensity has no effect on tax avoidance. Financial performance as proxied by Return on Assets (ROA) cannot moderate the effect of deferred tax on tax avoidance, financial performance can moderate the effect of fixed asset intensity on tax avoidance.